(untitled) (Discourse of Law and Administration, 2023)
The article discusses the basic documents of the European Commission for Democracy through Law (Venice Commission) dealing generally with the rule of law and judicial independence as one of its main guarantees and the Venice Commission’s opinions concerning the situation in Hungary and Poland. There is author´s personal experience as a rapporteur of some of these opinions. The article offers a summary of the principal reasons why it has been quite easy to attack judicial independence in these countries and how it has happened. The article also contains the description of the rule of law as one of the foundations of the European Convention for the Protection of Human Rights and Fundamental Freedoms and the analysis of the recent decision of the European Court of Human Rights in the case of Grzęda v. Poland and the conclusions the Court has drawn in relation to the issue of the rule of law.